Vanadium salt inhibits osteoclast formation and preserves bone integrity in a rat model of type-1 diabetes associated bone loss - Joshua Greendyk; James Thornton; Darian Napoleon; Michael Greenberg; Anthony Lin; Mike Levidy; Jonathan R. Lopez; Maximilian Muñoz; Kevin Innella; Yazan Kadkoy; Maya Deza Culbertson; Jessica A. Cottrell; et al. (BioMetals, 2026)

Wild bees occupy temporally stable pollen nutritional niches - Anthony D. Vaudo; Jillian A. Luthy; Eva Lin; Sonja K. Glasser; Anne S. Leonard (Oecologia, 2026)
As bees’ primary source of protein and lipids, pollen is a nutritional resource key to the persistence of wild populations. Because bee taxa may differ in their pollen macronutrient requirements, and pollen is a limited resource that varies chemically across plants, nutritional niches may shape bees’ ecological interactions. To explore whether members of bee communities occupy pollen nutritional niches, we analysed the protein and lipid content of pollen collected by abundant bee subgenera ( Nomadopsis , Melanosmia , Eumelissodes , Pyrobombus ) and observed their pollen-collecting visitation to plant species at a single Sierra Nevada meadow across three years. We compared pollen nutrition and host plant visitation among subgenera, and at the species level within Pyrobombus. Subgenera exhibited clear and temporally consistent separation of pollen load macronutrition each year, achieved by either host-plant fidelity or flexibility when foraging. Pyrobombus species shared a nutritional niche, potentially creating competition for pollen macronutrients among species relieved by their taxonomic flexibility. These results offer some of the first evidence that nutritional niches among wild bee taxa are annually stable and demonstrate how different taxa may forage to achieve nutritional consistency. Relevant to bee conservation, our findings emphasize that a nutritionally diverse array of plants may be required to support wild bee communities.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Reconstructing the invasion history of the bark beetles Orthotomicus erosus and Cyrtogenius luteus (Coleoptera, Curculionidae, Scolytinae) in South America - Leonel Stazione; Carolina Soliani; Anthony Cognato; Demian F. Gomez; Dimitrios Avtzis; Edgar Eskiviski; Gonzalo Martinez Crosa; Wei Lin; You Li; Juan Corley; Victoria Lantschner (Biological Invasions, 2026)

Electrolytic hydrogen production from acidified wastewater effluent - Lin Du; Jinyue Jiang; Guangye Zhou; Yuqing Yan; Ryan S. Kingsbury; Anthony Y. Ku; Zhiyong Jason Ren (Water Research, 2026)

Does your job really matter? Job-specific cancer incidence among a cohort coal mine workers in Queensland, Australia - Deborah Catherine Glass; Stella May Gwini; Anthony Del Monaco; Lin Fritschi; Michael J. Abramson; Malcolm Ross Sim; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2026)
Purpose Globally, coal production exposes millions of workers to coal mine dust. This study aimed to measure overall and site specific cancer incidence among coal mine workers (CMW) who performed different types of work. Methods A retrospective cohort of CMW in Queensland, Australia, was assembled using health assessment records from 1992. CMW were grouped by job type and then into Work Categories and linked to the Australian Cancer Database up to 2016. Standardized cancer incidence ratios (SIR) and relative cancer incidence ratios (aRIR) within the cohort, adjusted for age, era, and smoking status, were calculated for men and women with Poisson regression. Results There were 5,568 cancers diagnosed among 146,553 men and 396 in 19,927 women. The overall cancer risk was comparable to that of the general population for most Work Categories. The risk of lung cancer was higher for male Production (SIR 123, 95% Confidence Interval [CI] 107–142; adjusted Relative incidence Ratio (aRIR) (adjusted for era, age and smoking status) 1.23, 95%CI 0.99-1.52) and Construction workers (SIR 189, 95%CI 31–272; aRIR 1.78, 95%CI 1.20–2.62) when compared with the Australian population and within the cohort after adjusting for smoking. Laryngeal cancer was increased in Production workers (SIR 145, 95%CI 100–212). Conclusions Increased rates of lung and laryngeal cancers were identified for male Production workers and lung cancer for Construction workers. These could be related to mine workplace exposures such as silica and diesel engine exhaust.

Conserved Ecological Responses to Novel Urban Stressors - Anthony A. Snead; Emerald Lin; Shira Linsk; Lena Olson; Kristin M. Winchell (Journal of Biogeography, 2025)
Aim As anthropogenic activities continue, species are exposed to climate change and rapid urbanisation that alter their distribution; however, the relative contributions of climate and anthropogenic influence on species distribution are unknown for most species. We use an environmentally sensitive salamander genus ( Eurycea ) that occupies urban and forested habitats to test the relative importance of temperature‐, precipitation‐ and urbanisation‐related variables before placing these results into a phylogenetic context. We aim to test the impact of climate and urbanisation in driving the distribution of the genus while evaluating patterns of niche conservatism. Location Nearctic. Taxon Eurycea (Plethodontidae, Lungless Salamanders). Methods We developed MAXENT niche models for 13 Eurycea species using bioclimatic and urbanisation‐related variables. We assessed the importance of these environmental variables through permutation importance and compared response curves to determine niche overlap. Phylogenetic analyses tested for evolutionary constraints on species responses to environmental factors. Results Climatic variables were the primary drivers of Eurycea distributions, while urbanisation‐related variables had lower overall importance. Phylogenetic analyses revealed that responses to urbanisation‐related factors, specifically impervious surface and human population density, exhibited significant phylogenetic signal, indicating a stronger evolutionary constraint on responses to urbanisation than to climate. While climatic variables showed limited phylogenetic conservatism, niche overlap analyses demonstrated that more closely related species had greater similarity in ecological responses to urbanisation than to climate. Evolutionary history influenced species' ecological tolerances, with some environmental responses more conserved than expected under Brownian motion. Main Conclusions Our findings highlight the role of evolutionary history in shaping Eurycea responses to environmental variation. While climatic factors predominantly influence broadscale distributions, urbanisation‐related responses are more evolutionarily conserved across the genus. These results suggest that past evolutionary trajectories may constrain species' capacity to adapt to novel anthropogenic stressors, underscoring the importance of incorporating phylogenetic perspectives in conservation strategies for Eurycea and other evolutionarily constrained taxa.

Contrasting wood carbon quality of angiosperms and gymnosperms drives fungal-mediated decomposition responses to nutrient enrichment - Zhiyuan Xu; Zhenhong Hu; Lin Jiang; Tianyi Qiu; Wenqian Li; Mark A. Anthony (Forest Ecology and Management, 2025)

Effects of tree geometry on the aerodynamics of sympodial trees with analysis of extreme gust wind - Pengfei Lin; Gang Hu; K.T. Tse; Anthony Kwan Leung (Agricultural and Forest Meteorology, 2025)

Nitrogen-doped hierarchical porous carbon derived from shea nut shell for high-performance supercapacitor and LiS battery - Daniel Nframah Ampong; Wang Lin; Felipe M. de Souza; Frank Ofori Agyemang; Anthony Andrews; Kwadwo Mensah-Darkwa; Ram K. Gupta (Next Research, 2025)

Targeted TGF-βR2 Silencing in the Retrotrapezoid Nucleus Mitigates Respiratory Dysfunction and Cognitive Decline in a Mouse Model of Cerebral Amyloid Angiopathy with and without Stroke - Ahmad El Hamamy; Zahid Iqbal; Ngoc Mai Le; Arya Ranjan; YuXing Zhang; Hung Wen Lin; Chunfeng Tan; Destiny Sumani; Anthony Patrizz; Louise D. McCullough; Jun Li (Translational Stroke Research, 2025)

Clearance of particles from regular-flavored little cigar smoke across lung lobes in female Sprague-Dawley rats - Kaisen Lin; Christopher Wallis; Patricia Edwards; Austin Cole; Laura Van Winkle; Anthony S. Wexler (Journal of Aerosol Science, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Long-term trends in heat wave gaps for the New York City metropolitan area - Anthony Lin; Brian A. Colle (Urban Climate, 2025)

Correction to: Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2025)

Relational characteristics and dynamics between high-tech firms in the Pearl River Delta and the empowerment for technological innovation by Hong Kong - Jili Xu; Anthony G. O. Yeh; George C. S. Lin; Xingjian Liu; Fan Fiona Yang; Zixin Luo (Journal of Geographical Sciences, 2025)

The feasibility of batch-wise polyester degradation and recycling using recombinant Escherichia coli expressing PHB depolymerase (PhaZ ) - Yen-Chun Lin; En Ze Linda Zhong-Johnson; Anthony J. Sinskey; Si-Yu Li (Journal of Environmental Management, 2025)

Evaluation of passive samplers as a cost-effective method to predict the impact of wildfire smoke in grapes and wines - Arran C. Rumbaugh; Chen Liang; Yan Wen; Andrey Khlystov; Dave Campbell; Christopher Wallis; Hao-Lin Fang; Anthony Wexler; Yeongkwon Son (Food Chemistry, 2025)

Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2024)

Profiles of brain topology for dual-functional stability in old age - Sa Zhou; Mia Anthony; Ehsan Adeli; F. Vankee Lin (GeroScience, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Experimental investigation on vibration characteristics of sympodial tree - Pengfei Lin; Gang Hu; K.T. Tse; Anthony Kwan Leung (Urban Forestry & Urban Greening, 2024)

Distribution of soil tardigrades as revealed by molecular identification across a large-scale area of Australia - Zi-Yang He; Hang-Wei Hu; Bao-Anh Thi Nguyen; Qing-Lin Chen; Anthony Weatherley; Michael Nash; Li Bi; Keren Wu; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

The different adsorption-degradation behaviors of SARS-CoV-2 by bioactive chemicals in wastewater: The suppression kinetics and their implications for wastewater-based epidemiology - Mohamed Bayati; Hsin-Yeh Hsieh; Shu-Yu Hsu; Sally Qasim; Chenhui Li; Anthony Belenchia; Jessica Klutts; Sally A. Zemmer; Kristen Sibley; Melissa Reynolds; Elizabeth Semkiw; Hwei-Yiing Johnson; et al. (Science of The Total Environment, 2024)

Utilization of shea butter waste-derived hierarchical activated carbon for high-performance supercapacitor applications - Daniel Nframah Ampong; Wang Lin; Felipe M. de Souza; Vikram Kishore Bharti; Frank Ofori Agyemang; Anthony Andrews; Kwadwo Mensah-Darkwa; Alisha Dhakal; Sanjay R. Mishra; Felio Perez; Ram K. Gupta (Bioresource Technology, 2024)

Characterizing wind-induced reconfiguration of coaxial branched tree - Pengfei Lin; Gang Hu; K.T. Tse; Jie Song; Anthony Kwan Leung; Zhenliang Jiang; Lianghao Zou (Agricultural and Forest Meteorology, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Neuromuscular fatigue and muscle damage following a simulated singles badminton match - Zengyuan Lin; Anthony J. Blazevich; Chris R. Abbiss; Jodie Cochrane Wilkie; Kazunori Nosaka (European Journal of Applied Physiology, 2023)
Purpose To understand muscle damage in badminton, changes in neuromuscular function were investigated after simulated badminton singles matches performed by ten state-level male players. Methods Each participant played eight matches and measurements were taken before, immediately after, and 1 and 24 h after each match. Maximal voluntary isometric contraction (MVC) torque of the knee extensors and flexors, voluntary activation (VA) during MVC and torques generated by doublet ( T Doublet ), 20 ( T 20 ) and 80 Hz ( T 80 ) electrical stimulations of the knee extensors were measured from the dominant leg (the racket-hold arm side). Muscle soreness was assessed by a 100-mm visual analogue scale from both legs. The number of lunges performed by each participant in each match was analysed by videos, and its relations to other measures were examined. Results Pre-match knee extensor and flexor MVC torques were 278.4 ± 50.8 Nm and 143.0 ± 36.2 Nm, respectively. Knee extensor MVC torque of the dominant leg decreased immediately (12.0 ± 2.9%) and 1 h post-match (16.0 ± 3.2%), but returned to baseline at 24 h post-match. VA (11.4 ± 2.9%), T Doublet (13.1 ± 6.0%), T 20 (31.1 ± 12.3%) and T 80 (25.5 ± 7.9%) decreased ( p < 0.01) immediately post-match but recovered by 24 h post-match. A significant correlation ( r = − 0.64, p < 0.01) was observed between the total number of lunges performed in a match (160–240 times) and the magnitude of decrease in MVC torque (6.4–14.7%). Muscle soreness developed more ( p < 0.05) for the dominant (51.5 ± 11.6 mm) than the non-dominant leg (18.8 ± 8.6 mm). Conclusion Muscle damage induced by singles badminton matches was minimal, but the more the lunges are performed, the greater the neuromuscular fatigue.

Microplastics in rivers along an urban-rural gradient in an urban agglomeration: Correlation with land use, potential sources and pathways - Alexander Kunz; Falk Schneider; Nixon Anthony; Hsin-Tien Lin (Environmental Pollution, 2023)

CCA identifies a neurophysiological marker of adaptation capacity that is reliably linked to internal locus of control of cognition in amnestic MCI - Lizbeth Peralta-Malváez; Adam Turnbull; Mia Anthony; Ehsan Adeli; F. Vankee Lin (GeroScience, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Dancing to a different tune: changing reproductive seasonality in an introduced chital deer population - Catherine L. Kelly; Lin Schwarzkopf; Iain J. Gordon; Anthony Pople; David L. Kelly; Ben T. Hirsch (Oecologia, 2022)
Male and female reproductive behaviour is typically synchronised. In species such as those in the family Cervidae , reproductive timing is often cued by photoperiod, although in females, it can be dependent on body condition. When a species is introduced to a novel environment, the environment changes, or responses of the sexes to such cues differ, asynchronous reproductive behaviour between males and females may occur. We investigated the seasonality of reproductive behaviour in introduced chital deer in northern Queensland by examining male antler phase in relation to female conception rates. We then analysed the influence of different variables likely to affect the timing of male and female reproductive physiology. The lowest percentage of chital in hard antler in any 1 month in this study was 35% (Fig. 1), but the average value was closer to 50%, thus there was a seasonal peak in antler phase linked with photoperiod. Females conceived at any time of year, but were strongly influenced by the amount of rainfall 3 months prior to conception. This resulted in varying conception peaks year-to-year that often did not correspond to the male’s peak in hard antler. In this system, a proportion of males and females were physiologically and behaviourally ready to mate at any time of the year. We predict that differences in the timing of the peaks between the males and females will lead to increased reproductive skew (variation in reproductive success among individual males). This pattern may select for different mating strategies or physiological mechanisms to increase reproductive success.

Effects of Biogas Slurry on Crop Yield, Physicochemical Properties and Aggregation Characteristics of Lime Concretion Soil in Wheat–Maize Rotation in the North China Plain - Jiao Tang; Anthony J. Davy; Wei Wang; Xihuan Zhang; Dafu Wu; Lin Hu; Jinzhong Yin (Journal of Soil Science and Plant Nutrition, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

A Mechanistic Understanding of Monoclonal Antibody Interfacial Protection by Hydrolytically Degraded Polysorbate 20 and 80 under IV Bag Conditions - Aadithya Kannan; Jamie Giddings; Shrenik Mehta; Tiffany Lin; Anthony Tomlinson; Kyle Ritchie; Ian Shieh; Miguel Saggu; Nidhi Doshi (Pharmaceutical Research, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Evaluating a Modified High Purity Polysorbate 20 Designed to Reduce the Risk of Free Fatty Acid Particle Formation - Nidhi Doshi; Kyle Ritchie; Tamanna Shobha; Jamie Giddings; Kathrin Gregoritza; Rosalynn Taing; Stephen Rumbelow; Jeff Chu; Anthony Tomlinson; Aadithya Kannan; Miguel Saggu; Si Kai Cai; et al. (Pharmaceutical Research, 2021)

EndoPil: A Magnetically Actuated Swallowable Capsule for Weight Management: Development and Trials - Phuoc Thien Phan; Anthony Meng Huat Tiong; Muneaki Miyasaka; Lin Cao; Hung Leng Kaan; Khek Yu Ho; Soo Jay Phee (Annals of Biomedical Engineering, 2021)

Root age influences failure location in grass species during mechanical testing - David Boldrin; Anthony Glyn Bengough; Zijian Lin; Kenneth Wilhelmus Loades (Plant and Soil, 2021)
Aims Root tensile tests are often rejected if failure location is outside the middle section of samples. This study aims to identify where and why failure occurs along a root axis, and hence to revisit current approaches to test-validity. Methods Roots from Festuca arundinacea; Lolium multiflorum; Lolium perenne were sampled from field-grown plants. Roots were tensile tested using a universal testing machine. Root samples were randomly allocated into two groups for testing. Group 1 roots were orientated with the older tissue closest to the top clamp, group 2 roots were orientated oppositely. Tensile strength, Young’s modulus and failure location were recorded for each sample. Results Lolium multiflorum roots were thinner and stronger than roots of Festuca arundinacea. Failure location in tensile tests depended significantly on tissue age with 75% of samples failing in the younger third of root tissue regardless of the root orientation in the testing frame. Only 7% of roots failed in the middle third of the sample. Conclusions Fibrous roots tested in tension were observed to consistently fail in the younger tissue along the root axis. Exclusion of samples which fail outside the middle region of the root axis needs re-evaluation for a range of species.

A Millifluidic Perfusion Cassette for Studying the Pathogenesis of Enteric Infections Using Ex-Vivo Organoids - Reid L. Wilson; Sarah A. Hewes; Anubama Rajan; Shih-Ching Lin; Carolyn Bomidi; Takanori Iida; Mary K. Estes; Anthony W. Maresso; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2021)

ManoMap: an automated system for characterization of colonic propagating contractions recorded by high-resolution manometry - Niranchan Paskaranandavadivel; Anthony Y. Lin; Leo K. Cheng; Ian Bissett; Andrew Lowe; John Arkwright; Saeed Mollaee; Phil G. Dinning; Gregory O’Grady (Medical & Biological Engineering & Computing, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Noninvasive ultrasound deep brain stimulation of nucleus accumbens induces behavioral avoidance - Lili Niu; Yanchen Guo; Zhengrong Lin; Zhe Shi; Tianyuan Bian; Lin Qi; Long Meng; Anthony A. Grace; Hairong Zheng; Ti-Fei Yuan (Science China Life Sciences, 2020)

A generic brain connectome map linked to different types of everyday decision-making in old age - Brian Rooks; Mia Anthony; Quanjing Chen; Ying Lin; Timothy Baran; Zhengwu Zhang; Peter A. Lichtenberg; Feng Lin (Brain Structure and Function, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

An Integrated Sensor-Model Approach for Haptic Feedback of Flexible Endoscopic Robots - Wenjie Lai; Lin Cao; Rex Xiao Tan; Yung Chuen Tan; Xiaoguo Li; Phuoc Thien Phan; Anthony Meng Huat Tiong; Swee Chuan Tjin; Soo Jay Phee (Annals of Biomedical Engineering, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Temperature effects on the activity, shape, and storage of platelets from 13-lined ground squirrels - Scott Cooper; Sarah Lloyd; Anthony Koch; Xingxing Lin; Katie Dobbs; Thomas Theisen; Matt Zuberbuehler; Kaley Bernhardt; Michael Gyorfi; Tanner Tenpas; Skyler Hying; Sarah Mortimer; et al. (Journal of Comparative Physiology B, 2017)

Histopathological changes in zebrafish embryos exposed to DLPCBs extract from Zhanjiang coastal sediment - Yunpeng Yu; Fanghong Nie; Anthony Hay; Hongying Lin; Yi Ma; Xianghong Ju; Dongliang Gong; Jinjun Chen; Ravi Gooneratne (Environmental Monitoring and Assessment, 2017)

Variation in nesting behavior of eight species of spider mites, Stigmaeopsis having sociality - Yutaka Saito; Yan-Xuan Zhang; Kotaro Mori; Katsura Ito; Yukie Sato; Anthony R. Chittenden; Jian-Zhen Lin; Younghae Chae; Takane Sakagami; Ken Sahara (The Science of Nature, 2016)

Limited diversity associated with duplicated class II MHC-DRB genes in the red squirrel population in the United Kingdom compared with continental Europe - Keith T. Ballingall; Angeline McIntyre; Zhenzhen Lin; Naomi Timmerman; Erik Matthysen; Peter W.W. Lurz; Lynsey Melville; Amy Wallace; Anna L. Meredith; Claudia Romeo; Lucas A. Wauters; Anthony W. Sainsbury; et al. (Conservation Genetics, 2016)

Three N-Glycosylation Sites of Human Acetylcholinesterase Shares Similar Glycan Composition - Miranda L. Xu; Wilson K. W. Luk; Kei M. Lau; Cathy W. C. Bi; Anthony W. M. Cheng; Amy G. W. Gong; Huangquan Lin; Karl W. K. Tsim (Journal of Molecular Neuroscience, 2015)

Gas Sorption and the Consequent Volumetric and Permeability Change of Coal I: Experimental - Wenjuan Lin; Anthony R. Kovscek (Transport in Porous Media, 2014)

Gas Sorption and the Consequent Volumetric and Permeability Change of Coal II: Numerical Modeling - Wenjuan Lin; Anthony R. Kovscek (Transport in Porous Media, 2014)

Water quality associated public health risk in Bo, Sierra Leone - David H. Jimmy; Abu J. Sundufu; Anthony P. Malanoski; Kathryn H. Jacobsen; Rashid Ansumana; Tomasz A. Leski; Umaru Bangura; Alfred S. Bockarie; Edries Tejan; Baochuan Lin; David A. Stenger (Environmental Monitoring and Assessment, 2013)

The Use of SU-8 Topographically Guided Microelectrode Array in Measuring Extracellular Field Potential Propagation - Jessica Ka-Yan Law; Chi-Kong Yeung; Lin Li; John Anthony Rudd; Sven Ingebrandt; Mansun Chan (Annals of Biomedical Engineering, 2012)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

A Protocol for Characterizing the Impact of Collateral Flow after Distal Middle Cerebral Artery Occlusion - Richard Anthony DeFazio; Sean Levy; Carmen L. Morales; Rebecca V. Levy; Hung W. Lin; Tatjana Abaffy; Kunjan R. Dave; Brant D. Watson; Miguel A. Perez-Pinzon; Victoria Ohanna (Translational Stroke Research, 2011)

Relationship between cardiopulmonary mortality and cancer risk and quantitative exposure to polycyclic aromatic hydrocarbons, fluorides, and dust in two prebake aluminum smelters - Melissa C. Friesen; Geza Benke; Anthony Del Monaco; Martine Dennekamp; Lin Fritschi; Nick de Klerk; Jan L. Hoving; Ewan MacFarlane; Malcolm R. Sim (Cancer Causes & Control, 2009)

Ambulatory migration in mites (Acari: Tetranychidae, Phytoseiidae) to new leaves of moso bamboo shoots - Yanxuan Zhang; Yutaka Saito; Jianzhen Lin; Anthony R. Chittenden; Jei Ji; Yukie Sato (Experimental and Applied Acarology, 2003)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)